2012
DOI: 10.1186/1471-2164-13-584
|View full text |Cite
|
Sign up to set email alerts
|

The complete swine olfactory subgenome: expansion of the olfactory gene repertoire in the pig genome

Abstract: BackgroundInsects and animals can recognize surrounding environments by detecting thousands of chemical odorants. Olfaction is a complicated process that begins in the olfactory epithelium with the specific binding of volatile odorant molecules to dedicated olfactory receptors (ORs). OR proteins are encoded by the largest gene superfamily in the mammalian genome.ResultsWe report here the whole genome analysis of the olfactory receptor genes of S. scrofa using conserved OR gene specific motifs and known OR prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
79
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(91 citation statements)
references
References 47 publications
(64 reference statements)
9
79
0
Order By: Relevance
“…The olfactory receptor gene family, one of the largest gene families in the porcine genome [25,33], is over-represented with 353 out of 545 genes overlapping with CNVRs (Additional file 5: Table S3D). Genes involved in immune response, for instance IFN (Alpha-8, 11, 14; Delta-2), IFNW1 , IGK ( V1D - 43 , V2 - 28 , V8 - 61 ), IL1B and PG3I , were often observed as variable in CN between individuals.…”
Section: Resultsmentioning
confidence: 99%
“…The olfactory receptor gene family, one of the largest gene families in the porcine genome [25,33], is over-represented with 353 out of 545 genes overlapping with CNVRs (Additional file 5: Table S3D). Genes involved in immune response, for instance IFN (Alpha-8, 11, 14; Delta-2), IFNW1 , IGK ( V1D - 43 , V2 - 28 , V8 - 61 ), IL1B and PG3I , were often observed as variable in CN between individuals.…”
Section: Resultsmentioning
confidence: 99%
“…The olfactory receptor gene superfamily is the largest in vertebrate genomes, which function in the reception of innumerable odour molecules in the environment. Previous studies have showed that CNVs are highly prevalent among human and other vertebrate OR genes [40], [41], [42]. Two qPCR assays with primers located in two defensins genes ( BD114 and DEFB110 ) were used for CNVR#50 validation.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-two of these coding genes and five novel pseudogenes are in olfactory gene clusters. Pigs are known to have a large olfactory receptor repertoire (Nguyen et al 2012), and this adds to the reported collection. Supplemental Figure S4 shows the improved assembly and annotation around one of the olfactory region clusters on Xq.…”
Section: Comparative X Alignmentsmentioning
confidence: 96%